Differential impacts of Cntnap2 heterozygosity and Cntnap2 null homozygosity on axon and myelinated fiber development in mouse - Cifuentes-Diaz, Carmen; Canali, Giorgia; Garcia, Marta; Druart, Mélanie; Manett, Taylor; Savariradjane, Mythili; Guillaume, Camille; Le Magueresse, Corentin; Goutebroze, Laurence (Frontiers in Neuroscience, 2023)
Over the last decade, a large variety of alterations of the CNTNAP2 gene, encoding Caspr2, have been identified in several neuronal disorders, including neurodevelopmental disorders and peripheral neuropathies. Some of these alterations are homozygous but most are heterozygous, and one of the current challenges is to estimate to what extent they could affect the functions of Caspr2 and contribute to the development of these pathologies. Notably, it is not known whether the disruption of a single CNTNAP2 allele could be sufficient to perturb the functions of Caspr2. To get insights into this issue, we questioned whether Cntnap2 heterozygosity and Cntnap2 null homozygosity in mice could both impact, either similarly or differentially, some specific functions of Caspr2 during development and in adulthood. We focused on yet poorly explored functions of Caspr2 in axon development and myelination, and performed a morphological study from embryonic day E17.5 to adulthood of two major brain interhemispheric myelinated tracts, the anterior commissure (AC) and the corpus callosum (CC), comparing wild-type, Cntnap2-/- and Cntnap2+/- mice. We also looked for myelinated fiber abnormalities in the sciatic nerves of mutant mice. Our work revealed that Caspr2 controls the morphology of the CC and AC throughout development, axon diameter at early developmental stages, cortical neuron intrinsic excitability at the onset of myelination, and axon diameter and myelin thickness at later developmental stages. Changes in axon diameter, myelin thickness and node of Ranvier morphology were also detected in the sciatic nerves of the mutant mice. Importantly, most of the parameters analyzed were affected in Cntnap2+/- mice, either specifically, more severely, or oppositely as compared to Cntnap2-/- mice. In addition, Cntnap2+/- mice, but not Cntnap2-/- mice, showed motor/coordination deficits in the grid-walking test. Thus, our observations show that both Cntnap2 heterozygosity and Cntnap2 null homozygosity impact axon and central and peripheral myelinated fiber development, but in a differential manner. This is a first step indicating that CNTNAP2 alterations could lead to a multiplicity of phenotypes in humans, and raising the need to evaluate the impact of Cntnap2 heterozygosity on the other neurodevelopmental functions of Caspr2.